Acromial Fractures in Reverse Shoulder Arthroplasty: A Clinical and Radiographic Analysis. (May 2018) - Werthel, Jean-David; Schoch, Bradley S; van Veen, Steven C; Elhassan, Bassem T; An, Kai-Nan; Cofield, Robert H; Sperling, John W
Background: The purpose of this study is to assess the incidence of acromial stress fractures in a population of reverse shoulder arthroplasties (RSA) and determine potential risk factors for fracture. Patients and Methods: Between August 2004 and December 2013, 1082 primary RSA were performed at a single institution. Twelve (1.11%) patients were diagnosed with a postoperative acromial stress fracture. This group was case-matched to a control group of 48 shoulders. Clinical and radiographic risk factors for fracture were assessed. Results: Compared to controls, fractures were less satisfied with their outcome despite equivalent American Shoulder and Elbow Surgeons scores, pain scores, and range of motion. Osteoporosis was significantly associated with acromial fractures ( P  = .027). A smaller lateral offset of the greater tuberosity, greater arm lengthening, and a thinner acromion were more common in the fracture group ( P  = .026, P  = .004, and P  = .008, respectively). Conclusions: In summary, postoperative acromial stress fractures appear to be incidental lesions with little influence on the outcome after RSA. The combination of a thin acromion and superior migration of the humeral head increase the risk of acromial fracture. Lateralized designs that do not excessively verticalize the deltoid line of pull on the acromion may decrease the risk of postoperative acromial fractures.